THE FEATHER MITES (ACARI; PTEROLICHIDAE) OF PSITTACINE BIRDS FROM MANUSELA NATIONAL PARK, SERAM ISLAND - Sri - Hartini (ZOO INDONESIA, 2007)
Psittacine or parrots are colorful birdswith large heads, powerful, hookedbeaks and strong flexible feet with twotoes pointing backwards (MacKinnon1988). They are popularly kept as petanimals because of their beautifulappearance or their ability to imitatehuman and other voices. Their dailycontact with human being mayprobably transmit bird diseases suchas virus and bacteria vectored by theirparasites. A great deal diseasesagents has been learned concerningectoparasites of birds from many partsof the world, such as Southeast Asia(McClure et.al. undated) and in SouthAmerica (Perez & Atyeo 1984) andAfrica (Zump 1961).